Numerical investigation of the effects of geotechnical parameters on building risk level due to mechanized tunneling in urban areas - Mohammad Ali Iranmanesh; Ali Arianfar (Numerical Methods in Civil Engineering)
In this study, the effects of some geotechnical parameters on the surface settlement curves due to mechanized tunneling and the corresponding risk on surface buildings are investigated through numerical analysis. The advanced constitutive law of Plastic Hardening is utilized to accurately reflect the Soil behavior in unloading. Using the surface settlement curves obtained from numerical analysis, the risk category of surface buildings are calculated and the effectiveness of each parameter on the risk level is investigated. The results show that the cohesion and friction angle do not have a remarkable effect on surface settlement and the corresponding risk. However, the amount of overburden and the soil elastic modulus considerably affect the surface settlement and the risk level subjected to the surface buildings. Recognizing the role of each parameter makes it possible to predict the potential risk on surface buildings and to optimize the approaches for mitigating these risks.